Prevention of Underage Marriage in the Perspective of Islamic Law and Laws and Regulations - Akram, Fayyadh; Mardiantari, Ani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This study examines the prevention of child marriage in the perspective of Islamic law and laws and regulations in Indonesia. Child marriage is still a serious problem that has an impact on educational, health, psychological, and child rights protection. Normatively, Islam places marriage as a sacred institution that aims to realize the benefit, peace, and sustainability of offspring. Meanwhile, Indonesia's positive law through changing the marriage age limit in Law Number 16 of 2019 is a progressive step in strengthening child protection. This study uses a juridical-normative approach with a conceptual analysis of the postulates of fiqh, maqāṣid al-syarī'ah, and national regulations related to child protection and marriage. The results of the study show that the prevention of child marriage is in line with the principles of maqāṣid al-syarī'ah, especially the protection of the soul (ḥifẓ al-nafs), reason (ḥifẓ al-'aql), heredity (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Therefore, the synergy between Islamic law and laws and regulations is an important instrument in reducing the rate of child marriage in Indonesia.